Timor-Leste Economic Report, April 2019 : Moving Beyond Uncertainty - World Bank Group (World Bank, Washington, DC, 2019)
The Timor-Leste Economic Report provides an up-to-date assessment of key economic developments, presents the World Bank's forecasts and outlook for Timor-Leste and provides an in-depth examination of selected policy issues relevant to Timor-Leste. The TLER is intended for a wide audience, including policymakers, business leaders, and the community of analysts and professionals engaged in Timor-Leste’s evolving economy.